Peranan LAZISMU dalam Mengentaskan Kemiskinan (Studi Kasus LAZISMU Kabupaten Bantul) - Putri, Lutdiyah Tri; Mahendra, Gerry Katon (Indonesian Journal Publisher, 2024)
Poverty remains a significant challenge in Indonesia, including in Bantul Regency, despite a decline in national poverty rates as of March 2023. This study evaluates the role of LAZISMU Bantul in addressing poverty through educational and economic empowerment programs. Employing a descriptive qualitative approach, data were collected via direct observations, in-depth interviews with key participants, and document analysis. The research framework integrates theories of poverty alleviation, community empowerment, and program evaluation, focusing on monitoring and impact assessment to understand program effectiveness.The findings highlight that programs such as Mentari and Sang Surya scholarships effectively reduce educational costs for underprivileged families and improve beneficiaries' academic performance. Economic empowerment initiatives, including support for UMKM (Micro, Small, and Medium Enterprises) and training programs like